Trends in artificial intelligence : PRICAI 2016 Workshops : PeHealth 2016, I3A 2016, AIED 2016, AI4T 2016, IWEC 2016, and RSAI 2016, Phuket, Thailand, August 22-23, 2016, Revised selected papers /: PRICAI 2016 Workshops : PeHealth 2016, I3A 2016, AIED 2016, AI4T 2016, IWEC 2016, and RSAI 2016, Phuket, Thailand, August 22-23, 2016, Revised selected papers. (2017) - Unknown
No abstract available